A Systematic Method to Evaluate the Shear Properties of Soil-Rock Mixture considering the Rock Size Effect - Minghui Ren; Guangsi Zhao; Xianhao Qiu; Qinghua Xue; Meiting Chen (Advances in Civil Engineering)
The soil-rock mixture (S-RM) is widely applied in the geotechnical engineering due to its better mechanical properties. The shear strength, an essential aspect of S-RM which governs the stability and the deformation, is rather necessary to be revealed properly. The extraordinary issue of S-RM compared to fine-grained soils is the grain size effect on the strength analysis. This paper proposes a systematic method to obtain the realistic shear strength of S-RM by detecting the rock size effect. Firstly, based on fractal theory, the rock size was determined as 5 mm by the multifractal property of granular size distribution. Then, based on 2 selected specimen sizes combining the engineering dimension, shear gaps (T) effect and specimen size effect on the shear strength of S-RM have been investigated. It is shown that the gap of the direct shear test decides the physical mechanism of particles forming the shear resistance of S-RM based on the variation of apparent cohesion and mobilized internal friction angle. Specimen size effect is weakened by the gap effect considering the boundary effect. Realistic and stable shear strength parameters of S-RM have been researched by a reasonable gap (0.2–0.4D, where D is the largest particle size).